A laboratory study of elastic and anelastic properties of Savonnieres limestone - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (EAGE, 2014)
A study of pore fluid effects on the elastic and anelastic properties of sedimentary rocks is important for seismic data interpretation and for monitoring the fluid movement during hydrocarbon extraction in producing fields. A significant portion of the world’s hydrocarbon reserves are found in carbonate reservoirs. An understanding of fluid effects on carbonate properties is essential to characterize these reservoirs accurately. We present the results of low-frequency (0.1 – 120 Hz) and ultrasonic (~ 0.5 MHz) laboratory measurements of the elastic and anelastic properties of n-decane- and water-saturated Savonnieres oolitic limestone (helium permeability – 61 mD, porosity – 29%) carried out at an differential pressure of 15 MPa which were complemented with indentation tests conducted under ambient conditions. The measurements displayed reduction of the Young and shear moduli when changing from dry to water saturation conditions. Our results demonstrate that the Gassmann theory can be applied to n-decane saturated limestone, but it might not always be applicable to the limestone saturated with water.